2009
DOI: 10.1002/term.137
|View full text |Cite
|
Sign up to set email alerts
|

Reverse remodeling is associated with changes in extracellular matrix proteases and tissue inhibitors after mesenchymal stem cell (MSC) treatment of pressure overload hypertrophy

Abstract: Changes in ventricular extracellular matrix (ECM) composition of pressure overload hypertrophy determine clinical outcomes. The effects of mesenchymal stem cell (MSC) transplantation upon determinants of ECM composition in pressure overload hypertrophy have not been studied. Sprague-Dawley rats underwent aortic banding and were followed by echocardiography. After an absolute decrease in fractional shortening of 25% from baseline, 1 x 10(6) MSC (n = 28) or PBS (n = 20) was randomly injected intracoronarily. LV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 33 publications
(35 reference statements)
0
24
0
1
Order By: Relevance
“…Matrix metalloproteinases (MMPs) are a group of essential molecules that maintain extracellular matrix (ECM) homeostasis and ECM remodeling plays a large role in regulating myocyte migration, differentiation, and regeneration (55). MSCs release a combination of various MMPs and tissue inhibitors that are involved in extracellular remodeling (245). Notably, the ratio of MMPs to tissue inhibitors can be modulated by overexpression of certain factors, which can reverse the process of cardiac remodeling (334,351).…”
Section: A Antifibrosis and Prosurvivalmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are a group of essential molecules that maintain extracellular matrix (ECM) homeostasis and ECM remodeling plays a large role in regulating myocyte migration, differentiation, and regeneration (55). MSCs release a combination of various MMPs and tissue inhibitors that are involved in extracellular remodeling (245). Notably, the ratio of MMPs to tissue inhibitors can be modulated by overexpression of certain factors, which can reverse the process of cardiac remodeling (334,351).…”
Section: A Antifibrosis and Prosurvivalmentioning
confidence: 99%
“…Three main mechanisms of action underlie the favorable actions of MSCs in disease: 1) reduction of fibrosis 69 , 2) Stimulation of angiogenesis 70 and 3) restoration of contractile function 66, 67 through engraftment 71 , differentiation and stimulation of endogenous cardiac stem cells to proliferate and differentiate 63 (Figure 3). These effects occur in concert and together lead to the replacement of scarred or dysfunctional myocardial tissue with contractile and perfused tissue 65, 66 .…”
Section: Introductionmentioning
confidence: 99%
“…Willems et al 90 showed that a 1,4-dihydropyridine inducer of type 2 TGF-β receptor (TGFBR2) degradation-1 (ITD-1) selectively enhanced the differentiation of uncommitted mesodermal cells to cardiomyocytes. Extensive studies in the field of bone and cartilage regeneration have shown us that mechanical forces and extracellular matrix components significantly influence MSCs 91 but also MSCs modulate the matrix by secreting metalloproteinases and their tissue inhibitors by shifting the balance towards domination of matrix-degrading effects 69 . This may require the secretion of hepatocyte growth factor 92 and heme oxygenase-1 93 by MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been theorized that hMSCs reduce cardiac fibrosis 15 and enhance angiogenesis 16 largely through paracrine signaling (PS) mechanisms. 17,18 Moreover, recent studies have demonstrated that hMSC PS can modulate cardiomyocyte ion channel/pump activity.…”
Section: Introductionmentioning
confidence: 99%